Impaired postprandial clearance of triacylglycerol-rich lipoproteins in adipose tissue in obese subjects. - Potts, J; Coppack, S; Fisher, R; Humphreys, S; Gibbons, G; Frayn, K (1995)
Adipose tissue is an important site of clearance of circulating triacylglycerol (TAG), especially in the postprandial period. Postprandial lipemia is usually increased in obesity. We studied the extraction of TAG from plasma and TAG-rich lipoproteins (TRLs) in subcutaneous adipose tissue in 11 control and 8 obese subjects before and after a mixed meal. Clearance of plasma TAG and very low-density lipoprotein (VLDL)-TAG was decreased in the obese subjects after an overnight fast. After the meal, chylomicron-TAG extraction increased in the control group whereas VLDL-TAG clearance decreased; these changes were not seen in the obese group, in whom the VLDL particles appeared to be better able to compete with the chylomicrons for clearance by lipoprotein lipase. In the control subjects, removal of TAG from the TRL in the postprandial period was accompanied by a shift toward addition of cholesterol to the high-density lipoprotein (HDL) fraction; this was not observed in the obese subjects. We conclude that disturbed TRL-TAG clearance in adipose tissue is related both to the elevated plasma TAG concentrations and the depressed HDL-cholesterol concentrations typical of obesity.